2018
DOI: 10.3390/ijerph15122872
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy Lifestyle and Nutritional Habits Are Risk Factors for Cardiovascular Diseases Regardless of Professed Religion in University Students

Abstract: To date, few studies have evaluated the possible association between religion and nutritional habits, lifestyle and cardiovascular risk in the university population. This study identified differences in the eating habits of Christian and Muslim university students and determined a possible association between the impact of religion on their lifestyles and the parameters related to cardiovascular risk. A cross-sectional study was performed with a sample population of 257 students (22.4 ± 4.76 year) at the campu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…There are many publications on lifestyle habits among university students [16][17][18][19][20][21]. However, in Saudi Arabia (KSA), there are scarcely any investigations depicting medical students' knowledge and their view of healthy lifestyle habits [22].…”
Section: Introductionmentioning
confidence: 99%
“…There are many publications on lifestyle habits among university students [16][17][18][19][20][21]. However, in Saudi Arabia (KSA), there are scarcely any investigations depicting medical students' knowledge and their view of healthy lifestyle habits [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our study found that sex-related differences in adherence to MD could also partially explain the sex-related CVR. Indeed, it is well known that sex [ 26 ] and nutritional habits [ 27 ] could impact CVR. Recent epidemiological research has highlighted the effectiveness of dietary patterns, rather than individual nutrients, in studying eating habits and formulating therapeutic strategies for preventing and treating non-communicable diseases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are, therefore, an important target population for the Nutrients 2023, 15, 4685 2 of 15 promotion of healthy lifestyles to reduce the risk of developing chronic non-communicable disease in adulthood [10]. The inadequate lifestyle associated with university life can have a negative impact on various cardiometabolic factors [11]. González Sandoval et al (2014) [12] found that among Mexican university students, 61.3%, 22.6% and 32.7% had elevated LDL-cholesterol levels (>100 mg/dL), elevated total cholesterol values (200 mg/dL) and overweight/obesity, respectively.…”
Section: Introductionmentioning
confidence: 99%